On the Ethnic Origins of African Development: Chiefs and Precolonial Political Centralization - Michalopoulos, Stelios (Acad Manag Perspect, 2015)
We report on recent findings of a fruitful research agenda that explores the importance of ethnic-specific traits in shaping African development. First, using recent surveys from Sub-Saharan African countries, we document that individuals identify with their ethnic group as often as with the nation pointing to the salience of ethnicity. Second, we focus on the various historical and contemporary functions of tribal leaders (chiefs) and illustrate their influence on various aspects of the economy and the polity. Third, we elaborate on a prominent dimension of ethnicity, that of the degree of complexity of pre-colonial political organization. Building on insights from the African historiography, we review recent works showing a strong association between pre-colonial centralization and contemporary comparative development both across and within countries. We also document that the link between pre-colonial political centralization and regional development -as captured by satellite images of light density at night-is particularly strong in areas outside the vicinity of the capitals, where due to population mixing and the salience of national institutions ethnic traits play a lesser role. Overall, our evidence is supportive to theories and narratives on the presence of a “dual” economic and institutional environment in Africa.